EFFECTS OF DESIGN PARAMETERS ON STATIC EQUIVALENT STRESS OF RADIAL ROLLING BEARINGS - Bozca, Mehmet (CZECH TECHNICAL UNIV PRAGUE, 2021)
The aim of this study is to theoretically investigate the effects of design parameters on the static equivalent stress of radial rolling bearings, such as the point contact case for ball bearings and line contact case for roller bearings. The contact pressure, contact area and von Misses stress of bearings are calculated based on geometrical parameters, material parameters and loading parameters by using the developed MATLAB program. To achieve this aim, both the maximum contact pressure p(max) and Von Mises effective stress sigma(VM) are simulated with respect to design parameters such as varying ball and roller element diameters and varying ball and roller element elasticity modulus. For the point contact case and line contact case, it was concluded that increasing the diameter of ball and roller elements results in reducing the maximum contact pressure P-max and Von Mises effective stress sigma(VM). Furthermore, increasing the elasticity modulus of the ball and roller elements results in increasing the maximum contact pressure A max and Von Mises effective stress sigma(VM) because of the decrease of contact area A. The determination of the diameter of the ball and roller elements and the selection of material are crucial and play an effective role during the design process. Therefore, bearing designers and manufacturers should make the bearing geometrical dimensions as large as possible and bearing material as elastic as possible. Furthermore, the stress-based static failure theory can also be used instead of the standard static load carrying capacity calculation. Moreover, Von Mises stress theory is also compatible with the finite element method.
Keywords: Ball bearing; point contact; roller bearing; line contact; contact pressure; Von Mises stress; LIFE; BALL; Engineering